Hubungan Pengetahuan Terhadap Sikap Remaja Putri Tentang Pemeriksaan Payudara Sendiri (SADARI) di SMA Negeri 3 Banjarbaru Tahun 2012 - Akhmad Mahyuni; Agus Rahmadi; Emma Fury Anggraeny; STIKES Husada Borneo; Alumni STIKES Husada Borneo (HB PRESS, 2013)
The average of breast cancer patients in Indonesia is 10 from 100.000 of women. The cause of breast cancer is not yet known, for that, it is important that early detection of abnormalities in the breast by doing breast self-examination as early detection of abnormalities in the breast. The purpose of the research was to determine the relationship of knowledge and attitudes of female adolescent about breast self-examination (BSE). This study used cross sectional approach that collected using a questionnaire chi square statistical test. Samples had taken by using a random sampling technique from’ the population of 219 female students. The analysis had conducted to determine the relationship between knowledge toward attitudes of independent and dependent variables of BSE. Data analyzed with univariate analysis of the frequency distribution of the dependent and independent variables as well as bivariate analysis using chi square test statistic with a significance level of 0.1. The results of this research showed there is no significant correlation between knowledge toward female adolescent attitudes about breast self-examination (BSE). Recommended improve counseling about breast self-examination for early detection of breast cancer.